The interference effects of multi-channel pion-pion scattering contributions to the final states of Ψ- and γ-meson family decays; European Physical Journal Web of Conferences (EPJ Web of Conferences); Vol. 130 : MESON 2016 – 14th International Workshop on Meson Production, Properties and Interaction, Krakow, Poland, June 2-7 2016 - Surovtsev Yu. S. Yury Stepanovich; Bydzovsky P.; Gutsche T. Thomas; Kaminski R. Robert; Nagy M. Miroslav; Lyubovitskiy (Lyubovitskij) V. E. Valery Efimovich (2016, 2016)
Title screen